2014
DOI: 10.1186/2110-5820-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimal care and design of the tracheal cuff in the critically ill patient

Abstract: Despite the increasing use of non-invasive ventilation and high-flow nasal-oxygen therapy, intubation is still performed in a large proportion of critically ill patients. The aim of this narrative review is to discuss recent data on long-term intubation-related complications, such as microaspiration, and tracheal ischemic lesions. These complications are common in critically ill patients, and are associated with substantial morbidity and mortality. Recent data suggest beneficial effects of tapered cuffed trach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 68 publications
0
21
0
4
Order By: Relevance
“…Therefore, it is necessary to accurately control the cuff pressure in the management of mechanical ventilation . The impact of continuous control of P cuff on tracheal ischaemic lesions is not fully clear, and previous studies (Nseir et al, ; Jaillette et al, ) have not found a significant effect of continuous control of P cuff on the incidence of intubation‐related tracheal damage. A previous systematic review (Nseir et al, ) found that continuous control of P cuff seems beneficial in reducing the incidence of VAP, yet no significant differences on duration of MV, MV‐free days, antimicrobial treatment, ICU stay or ICU mortality have been found, which is similar to our findings.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, it is necessary to accurately control the cuff pressure in the management of mechanical ventilation . The impact of continuous control of P cuff on tracheal ischaemic lesions is not fully clear, and previous studies (Nseir et al, ; Jaillette et al, ) have not found a significant effect of continuous control of P cuff on the incidence of intubation‐related tracheal damage. A previous systematic review (Nseir et al, ) found that continuous control of P cuff seems beneficial in reducing the incidence of VAP, yet no significant differences on duration of MV, MV‐free days, antimicrobial treatment, ICU stay or ICU mortality have been found, which is similar to our findings.…”
Section: Discussionmentioning
confidence: 95%
“…32 Some newer tube designs have also incorporated an ultrathin (7 m) polyurethane cuff that greatly reduces fluid leakage in vitro. 67 Combining subglottic drainage tubes with the polyurethane cuff design decreased VAP by 64%. 72 A recent meta-analysis of 13 randomized clinical trials estimated a risk reduction of 45% and delayed onset of VAP by an average of 2.7 d in those managed with subglottic drainage tubes.…”
Section: Modifiable Risk Factors For Ventilator-associated Pneumoniamentioning
confidence: 99%
“…66 The predominant source of VAP is chronic microaspiration of oropharyngeal secretions pooled above the ETT cuff that occurs in as many as 88 -100% of intubated patients. 67,68 These secretions accumulate in the subglottic space and therefore cannot be effectively removed by suctioning the oral cavity. The volume capacity of this space is ϳ10 mL, and the accumulation of large secretion volumes (100 -150 mL/d) has been reported.…”
Section: Pathophysiology Of Ventilator-associated Pneumoniamentioning
confidence: 99%
“…2,3 Excessive cuff pressure may cause severe ischemic damage to the tracheal mucosa, potentially leading to granuloma, stenosis, or necrosis, whereas insufficient pressure and sealing may favor aspiration and promote ventilator-associated pneumonia. 4,5 Maintaining tracheal cuff pressure in an optimal range is therefore recommended and should be considered as an important part of a global protective ventilator strategy.…”
Section: Tracheal Cuff Management As Part Of a Lung-protective Strategymentioning
confidence: 99%